Cellular and molecular features of skeletal muscle growth and plasticity - Dal-Pai-Silva, Maeli [UNESP]; Zanella, Bruna Tereza Thomazini [UNESP]; Da Silva Duran, Bruno Oliveira [UNESP]; De Almeida, Fernanda Losi Alves; Mareco, Edson Assunção; De Paula, Tassiana Gutierrez [UNESP] (Elsevier, 2019)
Knowledge about the morphological, biochemical, and molecular features of skeletal muscle tissue in fish is important to better understand the control of muscle maintenance, development, and growth. Skeletal muscle is capable of phenotypic adaptation to extrinsic and intrinsic factors by changing the balance between muscle catabolism and anabolism, which can alter muscle plasticity. This chapter discusses the cellular and molecular features of skeletal muscle morphophysiology as well as the development and postembrionary muscle growth.
Keywords: Anabolism; Catabolism; Cell culture; Fish; MicroRNAs; Muscle growth; Myogenesis; Skeletal muscle